2020
DOI: 10.3389/fmed.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Liver Function in Liver Tumors Patients: The Performance of T1 Mapping and Residual Liver Volume on Gd-EOBDTPA-Enhanced MRI

Abstract: Purpose: To assess the performance of T1 mapping and residual liver volume (RLV) on Gd-EOBDTPA-enhanced MRI in pretreatment estimation of liver function in patients with liver tumors. Indocyanine green retention rate at 15 min (ICG R-15) was used as a reference standard. Methods: Ethical approval from the institutional review board and informed consent were obtained for this prospective study. We enrolled 155 patients with liver tumors who underwent pretreatment Gd-EOB-DTPA-enhanced MRI. T1 relaxation time bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Regrettably, that study did not consider the different sizes of different liver segments. However, several studies have demonstrated that liver volume-adjusted rrT1 values correlated better with ICG-PDR ( 65 ) and ICG-R15 ( 67 ) than the rrT1 values alone. In addition, Yoon et al indicated that the combined value of T1 and liver volume, adjusted for patient weight, could serve to identify patients with CP-A cirrhosis at high risk of decompensation ( 81 ).…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regrettably, that study did not consider the different sizes of different liver segments. However, several studies have demonstrated that liver volume-adjusted rrT1 values correlated better with ICG-PDR ( 65 ) and ICG-R15 ( 67 ) than the rrT1 values alone. In addition, Yoon et al indicated that the combined value of T1 and liver volume, adjusted for patient weight, could serve to identify patients with CP-A cirrhosis at high risk of decompensation ( 81 ).…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
“…In patients scheduled for hepatectomy, to avoid PHLF, it is necessary to assess the precise liver function of the remnant liver, especially in those with liver diseases ( 82 ). By combining rrT1 with the remnant liver volume, good diagnostic accuracy was obtained ( 67 ). Additionally, Huang et al showed the importance of the rrT1 value of the liver remnant, where the rrT1 value of the remnant was an independent risk factor for major postoperative complications ( 83 ); specifically, in patients who have undergone a major partial hepatectomy, the lower the rrT1 value, the higher the risk of a postoperative complication was.…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
“…The results of our study have revealed that the estimation liver function using MRI corelates with the MELD-Na score and there is statistically significant difference between the MRI estimated liver function of normal and cirrhotic livers. Any chronic insult to the liver parenchyma may result in hepatocellular injury that later leads to development of fibrosis, with continued progression resulting in cirrhosis and consequently hepatic synthetic function impairment [8]. There are several scoring systems for the clinical estimation of hepatic synthetic function in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical detail of MRI also enables one step examination of focal liver lesions, surgical planning and liver function [6]. The double dose approach has been proposed for the use of hepatobiliary contrast agent Gadoxetic acid to achieve an improved T1 relaxation time shortening for the assessment of HCC in cirrhotic patients [8]. The aim of this study is to retrospectively evaluate the role of Gadoxetic acid in the estimation of liver function and correlate this with MELD Na scores in patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al [ 109 ] reported that T1 mapping on gadoxetate-enhanced MRI provided information on global liver function and demonstrated functional heterogeneity in patients with HCC. Other studies have combined liver volume with hepatocyte function, and their results showed that combined T1 mapping and residual liver volume on gadoxetate-enhanced MRI could assess liver function with good diagnostic accuracy in patients with liver tumors[ 110 - 112 ]. Kim et al [ 113 ] and Wang et al [ 114 ] reported that the combination could predict post hepatectomy liver failure better than the ICG clearance test in patients with HCC who underwent hepatectomy.…”
Section: Focal Liver Lesionsmentioning
confidence: 99%